Formulation and Evaluation of Orally Disintegrating Tablets of Antihypertensive Drug Naftopidil - Gupta, Khem chand; Indrajeet, Singhvi (Asian Journal of Pharmaceutical Research and Development, 2015)
In the present work, orally disintegrating tablets of naftopidil were designed with a view to enhance patient compliance. A combination of superdisintegrants i.e sodium starch glycolate and crospovidone XL were used along with directly compressible mannitol to enhance mouth feel. The prepared batches of tablets were evaluated for hardness, weight variation test, friability, wetting time, disintegration time and In-vitro drug release studies. The prepared tablets were characterized by DSC studies. Different formulations showed disintegration time in the range of 20 to 37 sec. Among all the formulation, F7 showed 97.98% drug release within 60 minutes and considered best among the other formulations. No chemical interaction between the drug and excipients was confirmed by DSC studies. The stability study was conducted as per ICH guidelines and the formulation (F7) was found to be stable, with insignificant change in disintegration time, wetting time and in-vitro drug release pattern. The results revealed that orally disintegrating tablets of the poorly soluble drug naftopidil showed enhanced dissolution and, hence, better patient compliance.